Oil production in the Arctic National Wildlife Refuge : the technology & the Alaskan oil context : summary. - United States. Congress. Office of Technology Assessment. (Washington, D.C. : Congress of the U.S., Office of Technology Assessment, 1989)
"OTA-E-395"--P. [4] of cover. "February 1989"--P. [4] of cover. Shipping list no.: 89-180-P. Includes bibliographical references. Mode of access: Internet.